2005
DOI: 10.4103/0378-6323.16783
|View full text |Cite
|
Sign up to set email alerts
|

Occupational contact dermatitis among the traditional ′tie and dye′ cottage industry in Western Rajasthan

Abstract: Red RC base and naphthol were the commonest allergens in the 'tie and dye' industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 2 publications
2
26
1
Order By: Relevance
“…Moreover, significant differences were found in the prevalence of OCD between the lathe and ironing workers (19.9%) and the managers (10.2%; p = 0.007) at clothing manufacturing factories, which has not been previously reported. A speculative explanation for this may be that all workers with CD were not patch tested in previous studies [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, significant differences were found in the prevalence of OCD between the lathe and ironing workers (19.9%) and the managers (10.2%; p = 0.007) at clothing manufacturing factories, which has not been previously reported. A speculative explanation for this may be that all workers with CD were not patch tested in previous studies [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…The available literature on the CD of workers in the clothing industry is very limited, whereby only two similar surveys on tie and dye industry workers have been previously conducted [11, 12], and in recent decades scarcely any related population-based studies on such workers have been reported. Occupationally relevant exposure in our study is similar to those in the textile dyes and leather tanning industries [2022].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occupational cases demonstrate common involvement of hands in many studies (12)(13)24). Lack of hand involvement is considered to mean reduced likelihood of work-related dermatitis in textile workers.…”
Section: Discussionmentioning
confidence: 99%